The Conflict between Bone Kingdom and the British Authority in South Sulawesi, 1812-1816 - Latif, Abd (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: This article aimed to discuss the conflict between Bone Kingdom and the British Authority in South Sulawesi, Indonesia, during the period of 1812 through 1816. The political dynamics in Europe toward the end of the 18th century and early 19th century had affected the political dynamics in all areas of their colonies. In 1811, the Netherlands had to hand over their sovereignty over the Dutch Indies to the Britain, including South Sulawesi in March 1812. Before the British force arrived in Makassar, Bone Kingdom was the main Dutch ally and supporter in handling the political affairs in South Sulawesi. When the British force started to consolidate their position in South Sulawesi, the Kingdoms of Bone, Ternate, and Suppa refused to join forces nor to support the British authority. The result of the research also revealed that the Kingdom of Bone, which had so far a great role in the political affairs in South Sulawesi, was not invited to participate in the plan of the power transfer from the Dutch to the British authority. Therefore, Bone considered that the transfer of powers in South Sulawesi from the Dutch to the British was illegal and could not be recognized. This challenge by Bone, Ternate, and Suppa had made the British unable to control the whole territories which were used to be under the Dutch control, i.e. âOostder Provincieâ or the Eastern Province and âNoorder Provincieâ or the Northern Province. During the British occupation, both Provinces was under the control of Bone; so, the British authority was concentrated in the City of Makassar.KEY WORDS: Kingdom of Bone, Britain, Rampegading palace, conflict, alliance, and Eastern Province and Northern Province in Sulawesi.About the Author: Dr. Abd Latif is a Senior Lecturer at the Department of History, Faculty of Humanities UNHAS (Hasanuddin University) in Makassar City, South Sulawesi, Indonesia. For academic purposes, the author can be contacted via his e-mail address at: latifunhas@hotmail.comHow to cite this article? Latif, Abd. (2014). âThe Conflict between Bone Kingdom and the British Authority in South Sulawesi, 1812-1816â in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.145-160. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 6, 2014); Revised (March 9, 2014); and Published (April 28, 2014).